Model selection and estimation in high dimensional regression models with group SCAD - Jiang-lun Wu (Statistics & Probability Letters, 2015)
In this paper, we study the oracle property of the group SCAD under high dimensional settings where the number of groups can grow at a certain polynomial rate. Numerical studies are presented to demonstrate the merit of the group SCAD.